2006
DOI: 10.1016/j.atmosenv.2005.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of unregulated pollutants from European gasoline and diesel passenger cars

Abstract: Abstract:Within the framework of the European Artemis project, the emissions of unregulated compounds were measured on new technology passenger cars. A sample of passenger cars was tested on a chassis dynamometer with constant volume sampling (CVS). The measurement of unregulated compounds comprised about 100 different VOC in the C 2 -C 6 and C 7 -C 15 range and carbonyl compounds. The sampling of these compounds was made using sorbent tubes followed by analysis with chromatography technology in liquid and gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 3 publications
8
51
1
3
Order By: Relevance
“…Caplain et al [4] mediram gases de escape diluído de veículos diesel usando cartuchos com DNPH, e verificaram que o formaldeído era o principal tipo de aldeído presente. Shiotani et al [5] mediram aldeídos (formaldeído, acetaldeído, acroleína e benzaldeído) de motores "off-road" em banco de provas.…”
Section: Revisão Bibliográficaunclassified
“…Caplain et al [4] mediram gases de escape diluído de veículos diesel usando cartuchos com DNPH, e verificaram que o formaldeído era o principal tipo de aldeído presente. Shiotani et al [5] mediram aldeídos (formaldeído, acetaldeído, acroleína e benzaldeído) de motores "off-road" em banco de provas.…”
Section: Revisão Bibliográficaunclassified
“…Caplain et al [1] provided the analysis that diesel engine exhaust gases consist mostly of aromatic hydrocarbons (75-93%), straight or branched chain alkanes (6-18%), and carbonyl compounds (0.1-2%). Siegl et al [25] found that methane was 33% of total hydrocarbon emissions from an engine fuelled with diesel fuel.…”
Section: Unregulated Componentsmentioning
confidence: 99%
“…Transportation is a major source of atmospheric pollutants [1]. Some substances emitted from vehicle exhausts constitute environmental and health hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography coupled with mass spectrometry (GC/MS) or with a flame ionization detector (GC/FID) is commonly used for measuring VOCs in vehicle exhaust. [4][5][6][7] Real-time measurements, however, cannot be performed using these techniques. A time-of-flight mass spectrometer (TOFMS) can measure numerous VOCs simultaneously.…”
Section: Introductionmentioning
confidence: 99%